Aroma volatiles components of 'Fuerte' Avocado (Persea americana Mill.) stored under different modified atmospheric conditions. Issue 1 (2nd January 2019) - Mahendran, Thevaki; Brennan, James Gerard; Hariharan, Ganeshamoorthy
ABSTRACT: Modified atmosphere (MA) storage have direct influence on biogenesis and releasing of aroma volatiles in the ripe fruits. A study was conducted to investigate the influence of MA storage on the volatile constituents of ripe avocados. Mature avocados (cv. Fuerte) were packed in four different packaging materials and the equilibrium gas composition developed within the packs were in perforated polyvinylchloride: SM-60 (Control: 20.8% O2  + 0.03% CO2 ), Micro-porous polypropylene: MY-15 (4.8% O2  + 8.4% CO2 ), Low density polyethylene: LPDE (7.7% O2  + 5.8% CO2 ) and Micro-porous polypropylene: MD-15 (9% O2  + 5.4% CO2 ). The MA packs of avocados were stored at 7°C for 4 weeks and were ripen at 20°C. The volatile compounds of ripe avocados were investigated by means of gas chromatography (GC) and GC-mass spectrometry. A total of 68 of components were identified among those butyl acetate, 3-hexenyl acetate, 2-hexenyl acetate and hexyl acetate were only detected from MA stored avocados. Therefore, the MA storage with suitable gas composition could be used as a novel technology to extend the shelf life without significantly ( p  > 0.05) affecting the volatile components of the avocados.